Current and future status of JAK inhibitors. Issue 10302 (28th August 2021) - McLornan, Donal P; Pope, Janet E; Gotlib, Jason; Harrison, Claire N
Summary: An enhanced understanding of the importance of Janus kinase (JAK) and signal transducer and activator of transcription (STAT) signalling in multiple disease states has led to an increasing applicability of therapeutic intervention with JAK inhibitors. These agents have revolutionised treatments for a heterogeneous group of disorders, such as myeloproliferative neoplasms, rheumatoid arthritis, inflammatory bowel disease, and multiple immune-driven dermatological diseases, exemplifying rapid bench-to-bedside translation. In this Therapeutics paper, we summarise the currently available data concerning the successes and safety of an array of JAK inhibitors and hypothesise on how these fields could develop.